The Effect of Mobile Application “Pergiene Care” On Improving Perineal Hygiene Among Adolescent Girls - Isna Rachma Fitriana; Lutfatul Latifah; Lita Heni Kusumawardani (JKG (JURNAL KEPERAWATAN GLOBAL), 2026)
Background: Perineal hygiene is a way to treat and maintain cleanliness of the genital area to preserve the health of reproductive organs. Knowledge and attitudes can improve perineal hygiene. This study aimed to determine the effect of a mobile application on knowledge and attitudes among adolescents about perineal hygiene for preventing vaginal discharge. Methods: This study used a quasi-experimental pretest and posttest with a control group. The sampling technique used was consecutive sampling, with 84 respondents divided into two groups of 42 each. The instrument used was the Perineal Hygiene Knowledge and Attitude Questionnaire. The data were analysed using the T-test and the Mann-Whitney U. Results: The study showed differences in the pre- and post-intervention knowledge and attitudes scores in the intervention group (p=0.001;<0.05). In the control group, there was no difference in the pre- and post-test scores of knowledge (p=0.884; p>0.05) and attitudes (p=0.343; p>0.05). The results of the knowledge and attitude post-test scores between the intervention and control groups were significantly different (p=0.001; p <0.05). Conclusion: The results of the study indicate that there was an increase in knowledge and attitudes towards perineal hygiene after providing health education through the “Pergiene Care” application. The Pergiene Care application can be used as an educational medium for adolescents to improve perineal hygiene.